Analisis Kadar Octyl Methoxycinnamate (OMC) Dalam Sediaan Gel Tabir Surya dengan Metode Spektrofotometri UV-Vis - Teta Astri Noviandari; Aditya (Universitas Gunadarma, 2025)
Indonesia is one of the countries with a tropical climate with temperatures around 18-38°C. Indonesia is experiencing an increase in temperature so it is recommended to use sunscreen. One of the ingredients in sunscreen preparations is an octyl methoxycinnamate compound that can protect the skin from UVB rays. Badan Pengawas Obat dan Makanan (BPOM) stipulates that the maximum concentration of octyl methoxycinnamate allowed in sunscreen cosmetic preparations is 10%. The purpose of this study was to determine the levels of octyl methoxycinnamate contained in sunscreen gel samples circulating in Cibinong Market by UV-Vis spectrophotometric method. This study used the UV-Vis spectrophotometric method that has been validated for the analysis of octyl methoxycinnamate levels in sunscreen gel preparations. Based on the optimization results, it was found that the optimal solvent to attract OMC was isopropanol as shown by the linear equation y = 0.1003x + 0.0111 (R2 = 0.9998). Validation of the analytical method includes specificity showing OMC standard at λmax 308.5 nm; linearity with concentrations of 2, 3, 4, 5, 6, and 7 μg/mL with a value of y = 0.1006x+0.0102 (R2 = 0.9999); accuracy is shown from the percent of recovery is 127.88%; 113.67%; 108.44%; precision is also shown with %RSD with measurements are 0.4283%; 0.1255%; 0.122%, respectively; BD value = 0.679 μg/mL, and BK value = 2.058 μg/mL. This study using three sunscreen gel samples obtained from shops in Cibinong market showed that all gel samples containing octyl methoxycinnamate did not exceed the specified concentration, where sample A was 2.81%; sample B was 0.96%; and sample C was 0.37%.